FOREIGN DIRECT INVESTMENT AND THE DEVELOPMENT OF SMALL TRANSITION ECONOMIES - Silvije Orsag; Dejan Mikarević; Bojan Baškot (Acta Economica, 2017)
Investments and therefore foreign direct investment (FDI) are one of the most important factors leading to the economic growth of countries. There are certain aspects of the neoliberal theoretical concept that often take on an unconditional and unequivocal view of the significance of foreign direct investment for the performance of the national economy of developing countries, that is, the economies that are in the process of transition. In this paper, we will present some research results that point to caution and some suspicion when adopting economic policies, with the emphasis on the inviolability of foreign direct investment as a safe generator of economic growth. We have performed a multiple regression analysis for three countries of the Western Balkans (Serbia, Montenegro and Bosnia and Herzegovina) and concluded that there is no quantitative base to claim the significance of foreign direct investment for the economic growth of these three transition countries. By using a panel regression approach, we tried to ensure a detailed analysis by overcoming the potential problem of the availability of adequate time series for controlled variables.